Comparative chromosome painting in fish using human sex chromosome probes - Nagpure, N S; Kushwaha, B; Srivastava, Satish K; Halder, A; Ponnaiah, A G (Indian Journal of Fisheries, 2011)
The study was undertaken to identify sex chromosomes in Channa punctatus using human sex chromosome specific paint probes. Although the probes could detect sex chromosomes in human metaphase spread, no hybridization signals were detected on any of the chromosomes in C. punctatus. The results of the present study indicated that human sex chromosome paint probes were not useful for detecting sex chromosomes in Channa punctatus.